Оцінка надійності паливного насоса високого тиску дизельного двигуна при експлуатації на різних видах пальних - Журавель, Дмитро Павлович; Журавель, Дмитрий Павлович; Zhuravel, Dmytro (ТДАТУ, 2020)
UK: В роботі отримані результати ступеня впливу різних видів пальних на надійність паливного насоса високого тиску паливної системи дизельного двигуна, використовуючи коефіцієнт готовності і технічного використання, як узагальнених показників надійності трактора в цілому. Аналіз запропонованої імовірнісної моделі надійності складної технічної системи дозволив виявити «слабку ланку» ПНВТ, які працювали на біопальних. Так, «слабкою ланкою» з точки зору надійності є ущільнення, середній ресурс яких становив 960 м.г., що в 4 рази менше в порівнянні з паливними системами, які працювали на дизельному пальному. Заміна інертних матеріалів ущільнень до агресивного середовища біопального дозволить підвищити надійність ПНВТ і паливної системи трактора в цілому. RU: В работе получены результаты степени влияния различных видов топлива на надёжность топливного насоса высокого давления топливной системы дизельного двигателя, используя коэффициент готовности и технического использования, как обобщённых показателей надёжности трактора в целом. Анализ предложенной вероятностной модели надежности сложной технической системы позволил выявить «слабое звено» ТНВД, работающих на биотопливах. Да, «слабым звеном» с точки зрения надежности являются уплотнения, средний ресурс которых составлял 960 м.ч.., что в 4 раза меньше по сравнению с топливными системами, работающими на дизельном топливе. Замена материалов уплотнений, которые инертны до агрессивной среды биотоплива позволит повысить надежность ТНВД и топливной системы трактора в целом. EN: Тhe work focuses on the development and justification of a set of measures to ensure the operational reliability of machines during their operation. Which includes methods for determining the reliability indicators of real machines; forecasting and operational management of their technical condition; substantiation of the volumes and frequency of repair and maintenance actions; optimal preventative replacement strategy; calculation of the need for spare parts; rational organization of technical operation. Operational reliability can be considered one of the most important characteristics of a machine that synthesizes a number of quality indicators that enable it to perform its functions without fail, when used for its intended purpose, to preserve for a long time, and also to restore working capacity with minimal labor, time and material resources. The results of the degree of influence of various types of fuel on the reliability of the high-pressure fuel pump of a diesel engine fuel system, as well as the availability and technical utilization coefficient, as generalized indicators of the reliability of the tractor as a whole, are obtained. It has been established that one of the ways to increase the availability and technical use of the tractor can be to replace structural materials of the diesel engine fuel system with inert to aggressive biodiesel fuel. An analysis of the proposed probabilistic reliability model of a complex technical system made it possible to identify the "weak link" of fuel injection pumps operating on biofuels. Yes, the weak chain in terms of reliability are seals, the average resource of which is 960 mph, which is 4 times less compared to diesel fuel systems. Replacing inert seal materials in an aggressive biofuel environment will improve the reliability of the high-pressure fuel pump and the fuel system of the tractor as a whole.
Оценка надёжности топливного насоса высокого давления дизельного двигателя при эксплуатации на различных видах топлив
Fuel pump reliability assessment high pressure diesel engine at operation on various types of fuel
Keywords: біопальне; моделювання надійності; паливна система; паливний насос високого тиску; ймовірність відмови; ймовірність безвідмовної роботи; коефіцієнт готовності; коефіцієнт технічного використання; биодизельное топливо; моделирование надежности; топливная система; топливный насос высокого давления; вероятность отказа; вероятность безотказной работы; коэффициент готовности; коэффициент технического использования; biodiesel; reliability modeling; fuel system; high-pressure fuel pump; failure probability; failure-free operation probability; availability coefficient; technical use coefficient